A comparison of two methods of foot health education: The Fremantle Diabetes Study Phase II. Issue 2 (April 2015) - Baba, Mendel; Duff, Jenny; Foley, Laurie; Davis, Wendy A.; Davis, Timothy M.E.
Highlights We compared written and interactive foot health education in type 2 diabetes. Written information was more effective at improving overall foot health. Interactive education promoted greater confidence in implementing preventive measures. Fear of amputation was common and unchanged by either intervention. The most effective foot care education should include both educational strategies.